Menstrual phase and ambient temperature do not influence iron regulation in the acute exercise period - Zheng, H.; Badenhorst, C. E.; Lei, T.-H.; Liao, Y.-H.; Che Muhamed, A. M.; Fujii, N.; Kondo, N.; Mundel, T. (American Journal of Physiology - Regulatory, Integrative and Comparative Physiology, 2021)
The current study investigated whether ambient heat augments the inflammatory and post-exercise hepcidin response in women, and if menstrual phase and/or self-pacing modulate these physiological effects. Eight trained females (age: 37±7 y; VO2max: 46±7 mL·kg-1·min-1; peak power output: 4.5±0.8 W·kg-1) underwent 20 min of fixed-intensity cycling (100 and 125 W) followed by a 30-min work trial (˜75% VO2max) in a moderate (MOD: 20±1 °C, 53±8% relative humidity) and warm-humid (WARM: 32±0 °C, 75±3% relative humidity) environment in both their early follicular (days 5±2) and mid-luteal (days 21±3) phases. Mean power output was 5±4 W higher in MOD than in WARM (p=0.02) such that the difference in core temperature rise was limited between environments (-0.29±0.18 °C in MOD, p<0.01). IL-6 and hepcidin both increased post-exercise (198% and 38%, respectively), however, neither were affected by ambient temperature or menstrual phase (all p>0.15). Multiple regression analysis demonstrated that the IL-6 response to exercise was explained by leukocyte and platelet count (r2=0.72, p<0.01) and the hepcidin response to exercise was explained by serum iron and ferritin (r2=0.62, p<0.01). During exercise participants almost matched their fluid loss (0.48±0.18 kg·h-1) with water intake (0.35±0.15 L·h-1) such that changes in body mass (-0.3±0.3%) and serum osmolality (0.5±2.0 mOsm·kg-1) were minimal or negligible, indicating a behavioral fluid-regulatory response. These results indicate that trained, iron sufficient women suffer no detriment to their iron regulation in response to exercise with acute ambient heat stress or between menstrual phases on account of a performance-physiological trade-off.